Optimization of water usage at irrigation area of pakis-malang regency-Indonesia by using linear programming - Montarcih Limantara, Lily; Bisri, Mohammad; Fajrianto, Rizq (International Journal of Engineering and Technology, 2019)
Irrigation area of Pakis-Malang Regency-East Java Province of Indonesia has water deficit mainly in dry season. This study intended to analyze the optimization of water usage by using linear programming. The optimization is regarding to the existing condition cropping pattern and the other four alternatives of the new ones. Method of water balance was used for comparing irrigation water requirement in every cropping pattern and water availibility. Result showed that the 51% of dependable discharge represented the available discharge in irrigation area of Pakis during the 10 last years (from 2006 until 2015). For this condition discharge, the suitable cropping pattern is the existing one with the cropping intensity in one year is as 252.756% and the benefit of agricultural yields is Rp. 45,734,799,598.Â